Exploration of The Principal's Transformational Leadership Style In Increasing Teacher Motivation - Ahmad Rifai Siregar; Jodi Mahmud Siregar; Nadya Ramadhani; Nur Halimah Matondang; Arif Rahman; Deny Setiawan (South Sulawesi Education Development (SSED), 2024)
This research explores the transformational leadership styles that principals employ in an effort to increase teacher motivation. Using a qualitative approach, this study seeks to understand in depth how school principals apply transformational leadership dimensions, such as idealistic influence, inspirational motivation, intellectual stimulation, and individual consideration, and analyze the impact on teacher motivation in carrying out duties and responsibilities. Data will be collected through participatory observations within the school environment, in-depth interviews with principals, teachers, and other stakeholders, as well as documentation studies of related documents. Data analysis will be carried out inductively, by identifying patterns, themes, and relationships that arise from the data obtained. This research is expected to provide a more comprehensive understanding of the implementation of transformational leadership styles by school principals in the context of education in Indonesia. Research findings can be a reference for school principals and other education stakeholders in formulating strategies and policies to increase teacher motivation, ultimately contributing to improving the overall quality of education.